Assessment of knowledge regarding ‘essential obstetrics care’ among rural pregnant women in Kancheepuram District of Tamil Nadu, India - S., Gopalakrishnan; R., Rama (International Journal Of Community Medicine And Public Health, 2017)
Background: The first step towards achieving the goals of Reproductive and Child Health programme is to create awareness and educate the pregnant women about salient features of essential & emergency obstetric care and neonatal care provided. Objectives: To assess the level of knowledge on essential obstetrics care among pregnant women in a rural area. Methods:This cross sectional study was done in a rural area of Kancheepuram District in Tamil Nadu State, using a sample size of 100 pregnant women, arrived based on the prevalence of knowledge on antenatal care available from literature. The participants were selected by simple random sampling and data collected regarding the knowledge on ‘essential obstetrics care’, using a structured interview schedule based on the Mother Child Protection card. Results: About 45% of the participants had adequate knowledge regarding antenatal care, 46% had adequate knowledge on danger signs and symptoms of pregnancy, but only 13% of them had adequate knowledge regarding obstetric care. Knowledge regarding obstetrics care was found to have significant association with the educational status of pregnant mothers. Conclusions:The knowledge gap found in this study points to the need for re-evaluation of the effectiveness of health education measures given through the health care delivery system and the need for improved / revamped content and quality of health education materials to create better awareness among the pregnant women.